Hyperemesis gravidarum and birth outcomes—a population‐based cohort study of 2.2 million births in the Norwegian Birth Registry. Issue 13 (10th September 2013) - Vandraas, KF; Vikanes, ÅV; Vangen, S; Magnus, P; Støer, NC; Grjibovski, AM
Abstract : Objective: To study associations between hyperemesis gravidarum (HG) and birth outcomes. Design: Population‐based cohort study. Setting: Norway. Sample: Singleton births in the Norwegian Birth Registry, 1967–2009 ( n  = 2 270 363). Methods: Multiple logistic regression was applied to study associations between HG and dichotomous outcomes; multiple linear regression to study associations between HG, birthweight and gestational length. Generalised estimating equations were applied to obtain valid standard errors. Sub‐analysis on data with available information on smoking was conducted (1999–2009). Main outcome measures: Small and large for gestational age (SGA/LGA), Apgar score after 5 minutes, very preterm and preterm birth (VPTB/PTB), perinatal death, stillbirth, neonatal death, birthweight and gestational length. Results: No associations between HG and adverse pregnancy outcomes were observed in crude analyses, except for VPTB (odds ratio [OR] 0.79, 95% CI 0.67–0.93). In adjusted analysis, HG was associated with perinatal death (OR 1.27, 95% CI 1.08–1.48). Inverse associations were observed between HG and VPTB (OR 0.80, 95% CI 0.68–0.94) and LGA (OR 0.95, 95% CI 0.90–0.99). Sub‐analyses showed no associations between HG and perinatal death (OR 1.29, 95% CI 0.91–1.83). The inverse associations between HG, VPTB and LGA were strengthened (OR 0.66, 95% CI, 0.48–0.91 and OR 0.86, 95% CI 0.79–0.93, respectively). Exposed babies had reduced birthweight and gestational length compared with unexposed, adjusted difference − 21.4 g and − 0.5 days, respectively. Adjustment for smoking slightly strengthened the impact of HG on birthweight. Conclusions: Inverse associations for HG and VPTB and LGA were observed. HG was associated with slight reductions in birthweight and gestational age.